2015
DOI: 10.1111/tmi.12638
|View full text |Cite
|
Sign up to set email alerts
|

The free delivery and caesarean policy in Morocco: how much do households still pay?

Abstract: Abstractbackground The Free Deliveries and Caesarean Policy (FDCP) entitles all women in Morocco to deliver free of charge within public hospitals. This study assesses the policy's effectiveness by analysing household expenditures related to childbirth, by delivery type and quintile.methods Structured exit survey of 973 women in six provinces at five provincial hospitals, two regional hospitals, two university hospitals and three primary health centres with maternity units.results Households reported spending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 9 publications
(9 reference statements)
1
24
0
Order By: Relevance
“…16 31 32 A study in Malawi interviewing patients undergoing hernia operations reported CE rates as high as 90% using a threshold of 10% of yearly income. 28 Various studies looking at injury and trauma care costs in Vietnam, India and Nigeria have reported CE rates of 60%, 30% and 86%, respectively, 25 and a study in Morocco looking at obstetric surgical care alone estimated CE rates of 88%, 33 while an emergency obstetric care study in Indonesia estimated CE at 68%. 34 The intercountry variability makes it difficult to draw comparative conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…16 31 32 A study in Malawi interviewing patients undergoing hernia operations reported CE rates as high as 90% using a threshold of 10% of yearly income. 28 Various studies looking at injury and trauma care costs in Vietnam, India and Nigeria have reported CE rates of 60%, 30% and 86%, respectively, 25 and a study in Morocco looking at obstetric surgical care alone estimated CE rates of 88%, 33 while an emergency obstetric care study in Indonesia estimated CE at 68%. 34 The intercountry variability makes it difficult to draw comparative conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Madagascar examined data from women undergoing cesarean section to extrapolate rates of impoverishing expenditure (IE) and catastrophic expenditure (CE) for all surgery as 77.4% to 86% and 78.8% to 95.1% respectively [ 23 ]. Catastrophic expenditure due to cesarean section has been estimated at 88% for the poorest quintile in Morocco [ 24 ] and between 1.6% and 22% in a single state in India [ 25 ]. Road traffic injuries have also been a focus of OOP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, maternal mortality in Africa - in particular in SSA, which has remained which is indicative of the poor quality of maternal services - progressively declined over the last three decades [73]. We argue that the comparatively high adverse outcome associated with CSD in SSA is associated with vigorous policies, including, for instance, general practitioners, non-MD training [74] or free or the levying of a nominal fee by governments for CSDs [75,76]. Unfortunately, some countries like Morocco, rapidly lead to an alarming peak rate [77] Hopeful Results in the Reduction of the CSD Trend: Lessons from China China, in particular, is paving the way to address the CSD epidemic.…”
Section: Intercontinental Comparison Of Csd Outcomesmentioning
confidence: 88%